Effect of structured supervised yoga on stress, anxiety, and depression during a pandemic situation among the population of an urban resettlement colony of Delhi: A quasi-experimental study - Suprakash Mandal; Puneet Misra; Shashi Kant; Meenu Sangral; Priyanka Kardam (Wolters Kluwer Medknow Publications, 2022)
Background: Increased level of stress has a potential impact on physical, mental, and social well-being. It was seen aggravated during the global pandemic situation of COVID-19. Aim: The aim of this study was to find the effect of a community-based structured yoga program on the level of stress, anxiety, and depression. Materials and Methods: This was a community-based quasi-experimental study of pre-post in type involving 26 adult participants without any preexisting morbidity. All of them were provided 12 weeks of structured yoga program of 50 min/session, ≥2 sessions/week. Psychometric questionnaire, Depression, Anxiety, and Stress Scale-21 (DASS-21), stress biomarker serum cortisol, C-reactive protein, erythrocyte sedimentation rate, and rate pressure product were used to assess the primary and secondary outcome variables. Results: A total of 26 participants (male: 6 and female: 20) were enrolled and 18 participants completed the follow-up assessment. The median number of yoga sessions attended was 22. At the end of 12 weeks, there was a significant reduction of the stress component of DASS-21 (p: 0.0018) and the serum cortisol level (p: 0.032). Other variables had a reduction but it was not significant. No adverse effect was reported by the participants. Conclusions: This community-based yoga study showed beneficial effects among the participants. The stress level was found reduced significantly. However, the sustainable effect needed to be assessed further.